2012
DOI: 10.1523/jneurosci.6141-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Core and Matrix Thalamocortical Projections in Human Sleep Spindle Synchronization

Abstract: Sleep spindles, which are bursts of 11–15 Hz that occur during non-REM sleep, are highly synchronous across the scalp when measured with EEG, but have low spatial coherence and exhibit low correlation with EEG signals when simultaneously measured with MEG spindles in humans. We developed a computational model to explore the hypothesis that the spatial coherence of the EEG spindle is a consequence of diffuse matrix projections of the thalamus to layer 1 compared to the focal projections of the core pathway to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
103
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 49 publications
9
103
0
2
Order By: Relevance
“…We found that the cortical network alone generated slow oscillation activity that was similar to recordings in vitro in cortical slices and isolated cortical slabs (Sanchez-Vives and McCormick, 2000;Timofeev et al, 2000). Thus, thalamic network was necessary to obtain in vivolike pattern of slow oscillation and to ensure that the synaptic reorganization described in this study occurs in the presence of the synchronized effect of matrix thalamic projections (Bonjean et al, 2012;Lemieux et al, 2014).…”
Section: Spontaneous Slow Oscillations In the Thalamocortical Networksupporting
confidence: 68%
See 2 more Smart Citations
“…We found that the cortical network alone generated slow oscillation activity that was similar to recordings in vitro in cortical slices and isolated cortical slabs (Sanchez-Vives and McCormick, 2000;Timofeev et al, 2000). Thus, thalamic network was necessary to obtain in vivolike pattern of slow oscillation and to ensure that the synaptic reorganization described in this study occurs in the presence of the synchronized effect of matrix thalamic projections (Bonjean et al, 2012;Lemieux et al, 2014).…”
Section: Spontaneous Slow Oscillations In the Thalamocortical Networksupporting
confidence: 68%
“…Experimental studies (SanchezVives and McCormick, 2000;Chauvette et al, 2010) revealed that Up states of the slow oscillations are more often initiated in layer V neurons. In our model, higher probability of Up-state initiation in layer V ( Fig.…”
Section: Spontaneous Slow Oscillations In the Thalamocortical Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for this complex topographic distribution are currently debated and include aspects of neocortical propagation and resonance, different contribution of thalamic nuclei and focal versus distributed TC projections from first-and higher-order thalamic nuclei [56] and the possibility of several spindle-generating loci [5]. Importantly, the local character of spindles is consistent with the observation of learning-induced local regulation of sleep waves [57], and, thus, represents a strong argument for a role of spindles in sleep-dependent memory consolidation.…”
mentioning
confidence: 99%
“…Nishida and Walker (17) showed that following procedural task learning, spindles were increased in the learning hemisphere with respect to the nonlearning hemisphere. More recently there has been a report that spindles recorded by magnetoencephalography, in contrast to those recorded by EEG, arise from multiple asynchronous generators (18), a result which may be explained by the interaction of core and matrix thalmocortical projections (19). The globally synchronous nature of spindles was further challenged by Nir et al (20) who used depth electrodes implanted in medial brain areas to show that the majority of sleep spindles are not synchronous across the brain but rather localized to a single brain area.…”
mentioning
confidence: 99%